Upaya Pembinaan Kemakmuran Mesjid Baitul Akhyar Sebagai Aset Keagamaan Terhadap Masyarakat Desa Peutow Kecamatan Aceh Timur Birem Bayeun - Roni, Muhammad (SEURAYA Jurnal Pengabdian Kepada Masyarakat, 2023)
The connection to the mosque has become one of the important symbols for the religion of Islam, both since the early days of the Prophet Muhammad's preaching journey and today. Even though the mosque is the most important symbol, this paper discusses the management and character of the mosque which has different descriptions according to the conditions and situation of the existence of the mosque without reducing the main function of the mosque as a place of worship. By using the ABCD method, namely Asset Based Community Development. From this study it was found that the mosque is a place of worship for Muslims whose function is to worship Allah SWT. Historically mosques were used as community centers, courts, and religious schools. This place of worship for Muslims is also often used as a place for learning Al-Quran education. In modern times, they also maintain their role as a place for teaching and religious debate because mosques are a religious asset of society. which seeks to realize social welfare and order through religious studies, because it has a role in the formation of Muslim character and cultural identity